(untitled) (Fiep Bulletin - online, 2011)
The main objective of this study was to measure the variables mean heart rate (MHR) and peak heart rate (PEF) in a group of footballers at the amateur level (Phase 1) and warm-up (Phase 2) of the party, with the To estimate the level of cardiovascular effort being done by those subjects in relation to players of similar or higher competitive level. A secondary objective was to describe some anthropometric characteristics as (weight, height,% fat,% lean mass) and the third and final objective was to measure maximum oxygen consumption (VO2 Max.) By an incremental test. We measured a total of 10 subjects (n = 10) who signed the agreement shared by the coaching staff. To measure the (FCP.) and (FCM) using 2 Polar ® Watches Cardiómetro Make Model RS200, 2 "Huinches" for each clock, 2 wristbands and a Multifunctional Balance ® Brand Model K6 KEITA which it was obtained, the Weight, height, fat mass (%) and lean mass (%) of each subject before each measurement. The VO2 max. Was obtained through the test of Leger. The results found that (FCM) was 128 ± 9.2 bpm. and during the match a value of 149 ± 11.5 bpm. The (FCP) presented during the heating values of 170 ± 13.6 bpm. and during the game an average of 202 ± 13.9 bpm. Among the most important conclusions which arrived this study suggests that the amateur level player makes a less cardiovascular strain as high as other competitive level soccer player, it is necessary to provide these subjects with a prior physical preparation to enable tolerate high cardiovascular strain and thus to some extent to prevent accidents of this nature.